Stock Market Capitalisation and Economic Growth in Nigeria (1991 – 2021) (Journal of Management and Social Sciences, 2023)
The study examined the relationship between Stock Market Capitalisation and economic growth in Nigeria. Specifically, the study aimed at examining the effect of stock market corporate bond on gross domestic product in Nigeria, examining the effect of government securities on gross domestic product in Nigeria and determining the effect of equities on gross domestic product in Nigeria. Secondary data from 1991 to 2021 were sourced from the Central Bank of Nigeria Statistical Bulletin. Multiple Regressions were used to analyse the data collected and Minitab statistical package were used to present the results. Findings revealed that there was a negative correlation between dependentand independent variables. Findings revealed that there was an overall significant relationship between the dependent and independent variables. The study therefore recommends that Stock Exchange Market should encourage Nigerian Investors to have the habit of investing greatly in Government Securities; this will have a good effect on Gross Domestic Product. Nigerian Exchange Group should make the Investors know the beauty of Corporate Bonds. Investors should be encouraged by the stock exchange market to invest greatly in Equities in order to have a high impact on the value of Gross Domestic Product.